A new filter in residuated lattices - Saeid, Arsham Borumand; Zahiri, Saeide; Pourkhatoun, Manijeh (Fırat University, 2015)
In this paper, we introduce the notion of node elements and nodal filters of residuated lattices. We define nodal filter of a residuated lattice as a node of the set of all filters in residuated lattices and we study their properties. Next, we investigate the relationships with the other types of filters and special sets in residuated lattice. Finally we obtain a characterization of the nodal filters in terms of congruences